Determination of Level of Forming of Cognitive Independence of Pre-School Children in Constructive Activity - Yuliya Demidova (Pedagogical Discourse, 2012)
In accordance with the topic of the article, the author focuses on examination of cognitive independence as the quality of personality. On the basis of conducted diagnostic technique, the author determined personal notion of  cognitive independence of pre-school children and underlined the influence of constructing on its forming.